Traditional Sports Week Project in Character Building of Students at the Elementary School Level - Rahman, Trio Deswa; Susilawati, Dewi (Sains Global Institut, Indonesia, 2024)
Traditional sports games play an important role in character building of students, especially in elementary school. This study aims to examine how traditional games can improve character values ​​such as cooperation, discipline, and sense of responsibility among students. The method used is a qualitative approach with data collection through observation and interviews with students and teachers. The results of the study indicate that through playing activities, students not only acquire physical skills, but also learn about the importance of social interaction and cultural values ​​contained in the game. Thus, the integration of traditional sports games in the education curriculum is expected to contribute significantly to the development of positive character in students. This study recommends that schools be more active in implementing traditional games as part of a character education strategy. This study aims to evaluate the influence of the Traditional Sports Project on the characteristics of students at SDN 19 Krui. The method used is qualitative with a case study approach. The results of the study indicate that traditional sports can form positive characteristics such as cooperation, discipline, and independence in students.